"Object Categorization: Reversals and Explanations of the Basic-Level Advantage" (Rogers & Patterson, 2007): A simplicity account. - Close, James; Pothos, Emmanuel M. (Quarterly Journal of Experimental Psychology, 2012)
T. T. Rogers and K. Patterson (2007), in their article "Object Categorization: Reversals and Explanations of the Basic-Level Advantage" (Journal of Experimental Psychology: General, 136, 451- 469), reported an impressive set of results demonstrating a reversal of the highly robust basic-level advantage both in patients with semantic dementia and in healthy individuals engaged in a speeded categorization task. To explain their results, as well as the usual basic-level advantage seen in healthy individuals, the authors employed a parallel distributed processing theory of conceptual knowledge. In this paper, we introduce an alternative way of explaining the results of Rogers and Patterson, which is premised on a more restricted set of assumptions born from standard categorization theory. Specifically, we provide evidence that their results can be accounted for based on the predictions of the simplicity model of unsupervised categorization.